Modulating iron metabolism and gut microbiota: the therapeutic potential of Chia Seed Oil in obesity-related diabetes - Li, Wencong; Zhang, Li; Wang, Xiangxiang (Frontiers in Microbiology, 2026)
IntroductionObesity-related diabetes is a significant global health concern, underscored by perturbations in iron metabolism and gut microbiota composition. This study investigates the mechanistic role of Chia Seed Oil (CSO), rich in omega-3 fatty acids, in suppressing iron metabolism pathologies and promoting gut microbiota alterations to mitigate obesity-related diabetes.MethodsUsing a high-fat diet-induced obesity model in male C57BL/6J mice, we aimed to explore the effects of CSO supplementation on metabolic outcomes, iron status, and gut microbiota diversity.ResultsOur findings suggest that CSO effectively regulates iron metabolism, evidenced by altered serum ferritin levels, hepcidin, and transferrin saturation, while promoting a diverse gut microbiota profile.DiscussionThe study elucidates the potential of CSO as a therapeutic agent in managing obesity-associated metabolic disorders by restoring iron homeostasis and fostering gut health. These results highlight the interconnectedness of dietary fat, iron metabolism, and microbiome dynamics in the pathophysiology of obesity-related diabetes, suggesting a multifaceted approach to treatment strategies.